Electrohydrodynamic printing of sub-microscale fibrous architectures with improved cell adhesion capacity - Bing Zhang; Jiankang He; Qi Lei; Dichen Li (Virtual and Physical Prototyping, 2020)
A solution-based electrohydrodynamic (EHD) printing strategy was developed to fabricate sub-microscale biopolymeric fibres to mimic the tiny architectures of native extracellular matrix (ECM) for enhanced cellular performance. It was found that when the working voltage was significantly reduced to 500 V, sub-microscale fibres as well as user-specific patterns with an average fibre size of 193 ± 51 nm can be stably EHD printed. The presented process is applicable to biocompatible polycaprolactone (PCL) for the fabrication of water-stable sub-microscale fibrous architectures. The resultant sub-microscale fibres exhibited unique capability to enhance cellular adhesion, spreading and orientation in comparison with conventional microscale fibres fabricated by conventional melt-based EHD printing. The EHD-printed fibres can be precisely stacked to form multilayer sub-microscale structures. The proposed solution-based EHD printing process provides a promising strategy to fabricate sub-microscale biopolymeric architectures that could be further functionalised by the incorporation of bioactive components for enhanced tissue regeneration.